2004
DOI: 10.1016/j.ydbio.2004.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of the kinesin-II subunit KAP from cilia to nuclei during the mitotic and ciliogenic cycles in sea urchin embryos

Abstract: KAP is the non-motor subunit of the heteromeric plus-end directed microtubule (MT) motor protein kinesin-II essential for normal cilia formation. Studies in Chlamydomonas have demonstrated that kinesin-II drives the anterograde intraflagellar transport (IFT) of protein complexes along ciliary axonemes. We used a green fluorescent protein (GFP) chimera of KAP, KAP-GFP, to monitor movements of this kinesin-II subunit in cells of sea urchin blastulae where cilia are retracted and rebuilt with each mitosis. As exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 79 publications
0
23
0
1
Order By: Relevance
“…Confocal microscopy of living cells confirmed that KAP-GFP-labeled particles can be observed to move in both directions along the length of the flagella, similar to that reported previously for KAP-GFP in the sensory cilia of the nematode, C. elegans (Signor et al, 1999). KAP-GFP signals have also been observed in blastula cilia of sea urchin embryos (Morris et al, 2004). Interestingly, the Chlamydomonas KAP-GFP subunit is more efficiently incorporated into the Kinesin-2 complex of the flagella than the fla3 mutant subunit, even though both are present at similar levels in the cell body.…”
Section: Rescue Of Fla3 Defects With Epitope-tagged Kap Sequencesmentioning
confidence: 97%
“…Confocal microscopy of living cells confirmed that KAP-GFP-labeled particles can be observed to move in both directions along the length of the flagella, similar to that reported previously for KAP-GFP in the sensory cilia of the nematode, C. elegans (Signor et al, 1999). KAP-GFP signals have also been observed in blastula cilia of sea urchin embryos (Morris et al, 2004). Interestingly, the Chlamydomonas KAP-GFP subunit is more efficiently incorporated into the Kinesin-2 complex of the flagella than the fla3 mutant subunit, even though both are present at similar levels in the cell body.…”
Section: Rescue Of Fla3 Defects With Epitope-tagged Kap Sequencesmentioning
confidence: 97%
“…The first fluorescent protein fusion movement of IFT was described by Orozco et al (1999) in the nematode Caenorhabditis elegans demonstrating the processive motion of IFT particles in living sensory neuronal cilia. Since that time a number of systems have been used to observe IFT imaging via fluorescent protein fusions including Chlamydomonas (Mueller et al , 2005), trypanosomes (Absalon et al , 2008), sea urchin (Morris et al , 2004), and cultured mammalian cell lines (Follit et al , 2006; Nachury et al , 2007; Tran et al , 2008). Central to these observations has been the ability to dissect particle velocities as well as distinctions between anterograde and retrograde motility.…”
Section: Rationalementioning
confidence: 99%
“…Several NLS-like sequences have been found on the KIF3A/KIF3B/KAP complex, and the KAP subunit has been observed to redistribute from cilia nuclei during the mitotic cycle40. It is likely that additional signals in KIF17 are required to promote ciliary rather than nuclear import.…”
mentioning
confidence: 99%